Workload, Emotional Intelligence, And Intellectual Intelligence On Employee Performance At Maranatha Christian University - Rahayu, Puspita Puji; Santosa, Sonny; Sampe, Ferdinandus; Hatta, Heliza Rahmania (SEIKO : Journal of Management & Business, 2023)
Maranatha Christian University is a university that is currently growing with a large number of employees. So it is necessary to evaluate the four factors. The purpose of this study was to evaluate the relationship between workload, intellectual intelligence, and emotional intelligence on employee performance. The results of the research will be used as a basis for determining the Institute's decisions in the placement of employees and balancing the workload in related departments. The results of the research will be used as material for study in decision making and mapping of human resources according to the performance of each employee. The research was carried out using a quantitative approach with a data collection tool using a questionnaire on 81 respondents carried out randomly (random sampling). Keywoard: Workload, Performance, Emotional intelligence, Intellectual Intelligence,Correlation.